Bài 2: Giải phương trình sau:
17) \(\frac{1}{x-1}-\frac{3x^2}{x^3-1}=\frac{2x}{x^2+x+1}\)
18) \(\frac{1}{x-1}+\frac{2x^2-5}{x^3-1}=\frac{4}{x^2+x+1}\)
19) \(\frac{x+4}{2x^2-5x+2}+\frac{x+1}{2x^2-7x+3}=\frac{2x+5}{2x^2-7x+3}\)
20) \(\frac{x+1}{x^2+x+1}-\frac{x-1}{x^2-x+1}=\frac{3}{x\left(x^4+x^2+1\right)}\)
17) \(ĐKXĐ:x\ne1\)
\(\frac{1}{x-1}-\frac{3x^2}{x^3-1}=\frac{2x}{x^2+x+1}\)
\(\Leftrightarrow\frac{x^2+x+1-3x^2-2x^2+2x}{\left(x-1\right)\left(x^2+x+1\right)}=0\)
\(\Leftrightarrow-4x^2+3x+1=0\)
\(\Leftrightarrow-\left(x-1\right)\left(4x+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\4x+1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\left(ktm\right)\\x=-\frac{1}{4}\left(tm\right)\end{cases}}\)
Vậy tập nghiệm của phương trình là \(S=\left\{-\frac{1}{4}\right\}\)
18) \(ĐKXĐ:x\ne1\)
\(\frac{1}{x-1}+\frac{2x^2-5}{x^3-1}=\frac{4}{x^2+x+1}\)
\(\Leftrightarrow\frac{x^2+x+1+2x^2-5-4x+4}{\left(x-1\right)\left(x^2+x+1\right)}=0\)
\(\Leftrightarrow3x^2-3x=0\)
\(\Leftrightarrow3x\left(x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\left(tm\right)\\x=1\left(ktm\right)\end{cases}}\)
Vậy tập nghiệm của phương trình là \(S=\left\{0\right\}\)
19) \(ĐKXĐ:\hept{\begin{cases}x\ne2\\x\ne3\\x\ne\frac{1}{2}\end{cases}}\)
\(\frac{x+4}{2x^3-5x+2}+\frac{x+1}{2x^2-7x+3}=\frac{2x+5}{2x^2-7x+3}\)
\(\Leftrightarrow\frac{x+4}{\left(2x-1\right)\left(x-2\right)}+\frac{x+1}{\left(2x-1\right)\left(x-3\right)}-\frac{2x+5}{\left(2x-1\right)\left(x-3\right)}=0\)
\(\Leftrightarrow\frac{x^2+x-12+x^2-x-2-2x^2-x+10}{\left(x-2\right)\left(x-3\right)\left(2x-1\right)}=0\)
\(\Leftrightarrow-x-4=0\)
\(\Leftrightarrow x=-4\)(TM)
Vậy tập nghiệm của phương trình là \(S=\left\{-4\right\}\)
20) \(ĐKXĐ:x\ne0\)
\(\frac{x+1}{x^2+x+1}-\frac{x-1}{x^2-x+1}=\frac{3}{x\left(x^4+x^2+1\right)}\)
\(\Leftrightarrow\frac{x+1}{x^2+x+1}-\frac{x-1}{x^2-x+1}-\frac{3}{x\left(x^2+x+1\right)\left(x^2-x+1\right)}=0\)
\(\Leftrightarrow\frac{x\left(x+1\right)\left(x^2-x+1\right)-x\left(x-1\right)\left(x^2+x+1\right)-3}{x\left(x^2+x+1\right)\left(x^2-x+1\right)}=0\)
\(\Leftrightarrow x^4+x-x^4+x-3=0\)
\(\Leftrightarrow2x-3=0\)
\(\Leftrightarrow x=\frac{3}{2}\)(TM)
Vậy tập nghiệm của phương trình là \(S=\left\{\frac{3}{2}\right\}\)